DERIVING THE NONLINEAR RISK‐BENEFIT ALGORITHM FOR RESERVOIRS - Thanakorn Uan‐On (2018)
ABSTRACT: The Nonlinear Risk‐Benefit (NRB) Algorithm includes risk as one of the objectives in a multiple‐objective optimization problem. The NRB Algorithm is derived by extending the Surrogate Worth Trade‐Off method to quadratic programming. This category of problem is common in water resources planning and design, especially multipurpose reservoir systems. Consequently, an example is given using the algorithm for optimally operating a multipurpose reservoir. Copyright © 1988, Wiley Blackwell. All rights reserved